Mediating Role of Co-Creation Strategy on the Relationship Between Business Model Innovation and Corporate Reputation: A Case Study on Indonesian Telecommunication Firms - Mihardjo, Leonardus WW; Elidjen; Alamsjah, Firdaus; Sasmoko (Journal of Technical Education and Training, 2019)
Industry 4.0 drives the changing phenomenon throughout all industries driven by digital technology. Digital technology has become an enabler in the innovation of business models. New capabilities are required to be developed, especially for incumbent firms, since new entries have more agility in establishing new business models to create value. Even though the incumbent firms have strong reputation, they need to develop new distinct capabilities to create value in the long run. The fastest way to develop new capabilities is through collaboration also known as co-creation. Co-creation is a form of economic strategy to bring mutual values from different parties as a mediating role in creating business model innovations. Since there are limited study on co-creation strategy in relation to corporate reputation and business model innovation, this paper aims to assess the mediating role of co-creation strategy on the relationship between business model innovation and corporate reputation. The unit of analysis is taken from Indonesian telecommunication firms with sample of 35 firms out of 445 firms using purposive sampling method. Smart PLS (Partial Least Square) is used as the analytical approach and solution in the study. Research results reveal that corporate reputation has an indirect effect on business model innovation, but a direct effect on co-creation strategy. Co-creation strategy also plays significant effect to business model innovation. Co-creation strategy is a moderator variable between business model innovation and corporate reputation. The paper provided insight that the enhancement of corporate reputation should be directed towards building co-creation strategy which will then help strengthen business model innovation article.